Chemical characterization of Arctic aerosol for investigating the multi-annual profile of anthropogenic and biogenic markers - Feltracco, Matteo (Università Ca' Foscari Venezia, 2021)
The present PhD thesis provides a broad information about the chemical characterization of the Arctic aerosol from 2013 to early 2019 collected at Ny Ålesund, Svalbard Island, Norway. The work aims to investigate the inter- and intra-annual variation of several water-soluble compounds in order to understand their potential sources, their transport processes and their chemical/physical transformation. Svalbard is Norway's northernmost region, and the archipelago is one of the northernmost land-areas in the world. The Svalbard archipelago is surrounded by two different water masses: the warm Atlantic water on the western side, and the cold Arctic water on the eastern side. The coastal current is the closest water mass, originating from the cold East Spitsbergen Current (ESC) and further west, warm and saline Atlantic Water (AW) flows as the West Spitsbergen Current (WSC). For these reasons, the Svalbard region is particularly interesting in regard to climate change. Ny Ålesund is a research community with up to 150 people living there in the summer, while only around 20-30 permanent people are there during winter months. Pollution sources in and around Ny Ålesund include power stations, cars, airplanes and water traffic, including small vessels and cruise ships. The limited local contamination makes Ny Ålesund an open laboratory to investigate the long range atmospheric transport from anthropic areas and also the local biogenic sources. Here, the size-distributions, source apportionment and transport processes of major ions, organic acids, free and combined amino acids, sugars and phenolic compounds were studied in the Arctic aerosols. This led to more than 70 species. The thesis also aims to develop a new method for the determination of combined amino acids and photo-oxidation products of α-pinene in aerosol to understand differences and analogies with free amino acids and to understand the possible emission sources of these biomarkers. The determination of ions, carboxylic acids, free amino acids and ...